Uma análise da representação midiática dos moradores do conjunto habitacional Mucajá - SOUZA, Hélida dos Santos de (UNIFAP – Universidade Federal do Amapá, 2022)
This article aims to analyze the social representations conveyed by macapaenses newspapers (Daily Amapá and G1 Amapá) concerning the inhabitants of the Housing Complex Mucajá. The first part takes place on an approach newspapers, their emergence and characteristics. In the second section, a discussion is carried around the theory of social representations (TRS). In the third item, point out some aspects related to housing development Mucajá. Subsequently, it discusses the concepts of violence and crime. Finally, it presents the analysis of materials from newspapers.